The differential impacts of markets for technology on the value of technological resources: An application of group‐based trajectory models. (January 2016) - Mani, Deepa; Nandkumar, Anand
Abstract : Research summary : This article uses Group‐Based Trajectory (GBT) Models to advance strategic management research, focusing on demonstrating the differential impacts of markets for technology on the value of technological capabilities. Group Based Trajectory (GBT) models, a statistical technique based on finite mixture models, can be used to discern heterogeneity based on an attribute of interest, especially when the heterogeneity changes or evolves over time, and when there is a lack of theoretical guidance to discern the basis of heterogeneity. We illustrate these advantages of GBT models in our study of how the moderating effect of markets for technology on the value of technological capability is itself moderated by firm types. We conclude with a discussion of potential uses of the method in strategic management research . Managerial summary : This article illustrates the use of Group-Based Trajectory Models in discerning heterogeneity in an attribute of interest, including firm resources, capabilities, strategies, and performance, especially when such heterogeneity changes or evolves over time. We illustrate these advantages of GBT models in an analysis of how the moderating effect of markets for technology on the value of technological capability is itself moderated by firm types. Specifically, we find that the performance of firms, whose strategic position is based on technological competence, is negatively impacted when MFT are extensive, whereas that of firms whose strategic position is also based on other complementary capabilities is relatively unaffected . Copyright © 2015 John Wiley & Sons, Ltd.